2020
DOI: 10.3390/jcm9082412
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hyperacusis and Tinnitus

Abstract: Many individuals with tinnitus report experiencing hyperacusis (enhanced sensitivity to sounds). However, estimates of the association between hyperacusis and tinnitus is lacking. Here, we investigate this relationship in a Swedish study. A total of 3645 participants (1984 with tinnitus and 1661 without tinnitus) were enrolled via LifeGene, a study from the general Swedish population, aged 18–90 years, and provided information on socio-demographic characteristics, as well as presence of hyperacusis and its sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 60 publications
5
58
1
2
Order By: Relevance
“…The clinical information of patients with MD and tinnitus phenotypes is detailed in (Supplementary Tables 1 and 2). A second independent tinnitus cohort of 97 individuals from Sweden was selected as a replication cohort: the Tinnitus Swedish Tinnitus Outreach Project (STOP) [17] which originates from the LifeGene study [18] . A subgroup of 34 individuals with severe tinnitus was also selected according to the THI ≥ 56 (Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical information of patients with MD and tinnitus phenotypes is detailed in (Supplementary Tables 1 and 2). A second independent tinnitus cohort of 97 individuals from Sweden was selected as a replication cohort: the Tinnitus Swedish Tinnitus Outreach Project (STOP) [17] which originates from the LifeGene study [18] . A subgroup of 34 individuals with severe tinnitus was also selected according to the THI ≥ 56 (Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies focus on patients with cognitive impairment (n = 7), such as patients with WS (7,15,25,26), autism (9,22), and Asperger's syndrome (AS) (36). In addition, some studies (n = 12) are specific to patients with other comorbidities [tinnitus (2,20,32,33,35,40,46), hearing disorders (HD) (10, 44), Bell 's palsy (24), attention deficit hyperactivity disorder (ADHD) (45) and complex regional pain syndrome related dystonia (CRPS related dystonia) ( 28 2). Additionally, all use the word hyperacusis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…But only 2 presented the same discomfort loudness (80 dB HL) (9,22). Different definitions were also used to diagnose hyperacusis (5,21,24,26,29,33,35,36,(38)(39)(40)(41)(43)(44)(45)(46)(47)(48). Coelho (27) used both the hyperacusis definition and the discomfort loudness to diagnose.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the presence of hyperacusis may intensify the severity of perceived tinnitus. Cederroth et al [ 34 ] also showed that hyperacusis is strongly associated with tinnitus, and the relationship increased with tinnitus severity. We have provided evidence that subjects with weak/mild, strong, or very strong tinnitus differ in terms of how they perceive loud sounds—the more severe the tinnitus, the more severe is the hyperacusis.…”
Section: Discussionmentioning
confidence: 99%